Jack Wagner - Planet News, Limited:::Creator::::::::::::
Lifelong Steinbeck friend Jack Wagner, standing in uniform with Houses of Parliament in background. Buildings damaged in during bombing of London in World War II. Wagner had the idea for "A Medal for Benny" and got Steinbeck to help write the script. Original is in the safe.